Building Students’ Refusal Awareness Using Movie - Siti Suharsih; Aisyah Hamidiyah (Universitas Bunda Mulia, 2020)
The strategy of refusal has been carried out in many ways. Since it deals with the strategy done through language, the result portrays culture which the language used. As English in Indonesia is still as foreign language, the teaching learning process does not present the actual use of the expression. Since the English taught in Indonesian Language way, the learners use the English expression in Indonesian culture. It will give impact to the language the learners use. They use English but in Indonesian language way of thinking. The condition or the context when the utterances produced will give different meanings. Understanding meaning from utterances is a rather difficult. In some utterance, the meaning is not conveyed clearly in the structure of the sentences but it is hidden. The context will help the listener understand the hidden meaning of an utterance. To understand the context, movie is chosen as the media. Movie is believed gives more advantages than other media. It can give good effect on the students’ language acquisition as stated by Gardner (1984) and Lazear (1992) cited in Lynch (2006) that an audio-visual approach is highly effective in both lowering learner affective filters (Krashen-Terrell, 1984) and in language acquisition and learning.